SCALE UP DAN UJI TEKNIS ALAT PENGERING TIPE FLUIDIZED BED [Scale Up and Technical Test of Fluidized Bed Dryer] - Suryadi -; Sukmawaty -; Guyup Mahardhian Dwi Putra (Jurnal Ilmiah Rekayasa Pertanian dan Biosistem, 2017)
The available Fluidized Bed dryer has low drying capacity so it is necessary to increase the dimensions to improve the drying capacity. This study aimed to increased the dimensions of the Fluidized Bed dryer, to determined the drying capacity, and to conducted technical tests. This research was conducted at Power and Agriculture Machinery, Faculty of Food and Agroindustrial Technology, University of Mataram. The method used in this research was experimental method with mathematical approach. The parameters used in this study was the scale parameter and technical test parameters. Scale Up Fluidized Bed dryer was done in the drying chamber which includes the dimensions of the drying chamber and drying capacity. Technical testing included air flow velocity, the minimum fluidization velocity, temperature, drying time and space dryer efficiency. The drying chamber is a cylinder with a diameter of 40 cm, height 200 cm and 0.1256 m2 area of the base. The capacity of the Fluidized Bed dryer before Scale Up was 4 kg and the capacity after Scale Up was 8 kg. The speed of air flow through the drying chamber was 3 m/s. The distribution of temperature during the drying process ranges between 40-50â„ƒ and 50-60â„ƒ. According to the research, the more the masses drained, the longer the time required to dry the material. The efficiency of the drying chamber mostly present in the temperature range of 50-60â„ƒ with a value of 94.04%.